Angiotensin II induces endoplasmic reticulum stress in podocyte, which would be further augmented by PI3-kinase inhibition - Ha, Tae-Sun; Park, Hye-Young; Seong, Su-Bin; Ahn, Hee Yul (Clinical hypertension, 2015)
Introduction Angiotensin II (Ang II) contributes to the pathological process of vascular structures, including renal glomeruli by hemodynamic and nonhemodynamic direct effects. On renal effects, Ang II plays an important role in the development of proteinuria and glomerulosclerosis by the modification of podocyte molecules and cell survival. In the present study, we investigated the effect of Ang II on endoplasmic reticulum (ER) stress in podocytes. Methods We cultured mouse podocytes with increasing doses of Ang II and evaluated ER stress markers by Western blotting. Results Ang II increased Bip protein, an ER chaperone, in a dose-dependent manner at 24 h, which was ameliorated by losartan, an angiotensin II type 1 receptor antagonist. Ang II also increased ER stress markers, such as phospho-PERK, phospho-eIF2α, and ATF4 proteins of podocyte, significantly in a dose-dependent manner at 24 h. Increased phospho-PERK and ATF4 proteins were further augmented by phosphoinositide 3 (PI3)-kinase inhibitor, LY294002, which suggested that Ang II could induce podocyte ER stress of PERK-eIF2α-ATF4 axis via PI3-kinase pathway. Discussion These studies suggest that Ang II could induce podocyte ER stress of PERK-eIF2α-ATF4 axis via PI3-kinase pathway, which would contribute to the development of podocyte injury induced by Ang II, and the augmentation of PI3-kinase would be a therapeutic target.